Kant on Being a Useful Member of the World and Universal Basic Income - Martin Sticker (Ergo, An Open Access Journal of Philosophy)
I argue that there are Kantian grounds to endorse a Universal Basic Income (UBI) and that Kant’s practical philosophy can contribute to current debates about the ethics of UBI. I will make two points that mutually support each other. Firstly, there is a pro tanto argument for Kantians to work towards a UBI. A UBI, more so than conditional welfare schemes, enables agents to live up to their duty to be a useful member of the world. This should be conceptualized as an indirect duty to implement a UBI. Secondly, Kant’s ethics suggests a way to tackle the most pressing ethical objection against a UBI, the unfairness or surfer objection. The requirement that agents be useful for others is ethical and thus cannot be enforced externally. Yet, there is rational pressure on agents to do their part. Kant and UBI advocates can learn a great deal from each other.